Kundasang local community's perceptions towards international tourists - Jinulis, Ecca Avylla (2015)
Kundasang town is one of the popular tourism destinations in Sabah and has received an increase of international tourists since 2010 until now. The increasing of tourists to Sabah could possibly generate benefits and also problems to the communities around Kundasang. The objectives of this study were to identify the socio-demographic profile of Kundasang local community and to determine the perceptions of local community towards international tourists. A total of 150 set of questionnaire was distributed at Kundasang town. The result shows that there were significant different answers between age group, occupation and monthly salary. Respondent who aged between 18-24 and 45-55 years old were agreed that tourism is not giving any trouble to local community. Moreover, skilled labor does not agree that tourists’ has intimidated them because they always see tourist during their daily work and they were happy that tourism has changed their life. Respondent with salary under RM1, 000 per month were agreed that they have difficulties in communicating with tourists while respondent with salary RM3, 000 – RM4, 000 per month agreed that tourists is a very friendly and polite guest that they want to see more of them coming to Kundasang.